Il Palatino tra il XVIII e il XIX secolo: Approfondimenti, interpretazioni e nuovi documenti - Santoro, Valentina (Römische Mitteilungen, 2024)
This article makes a new contribution to the lengthy research recently conducted in the State Archive of Naples about the 130-year long era when the Bourbons owned the Farnese Gardens on the Palatine hill. Extra information has been found and fresh discoveries have been made in the Neapolitan and other archives. By analyzing the considerable amount of documents, the otherwise long-forgotten ruins of the Palaces of the Emperor are revealed in an additional depth of detail, covering some length of time.